CLSTN3 gene variant associates with obesity risk and contributes to dysfunction in white adipose tissue - Ningning Bai; Xuhong Lu; Li Jin; Miriayi Alimujiang; Jingyuan Ma; Fan Hu; Yuejie Xu; Jingjing Sun; Jun Xu; Rong Zhang; Junfeng Han; Cheng Hu; et al. (Elsevier, 2022)
Objective: White adipose tissue (WAT) possesses the remarkable remodeling capacity, and maladaptation of this ability contributes to the development of obesity and associated comorbidities. Calsyntenin-3 (CLSTN3) is a transmembrane protein that promotes synapse development in brain. Even though this gene has been reported to be associated with adipose tissue, its role in the regulation of WAT function is unknown yet. We aim to further assess the expression pattern of CLSTN3 gene in human adipose tissue, and investigate its regulatory impact on WAT function. Methods: In our study, we observed the expression pattern of Clstn3/CLSTN3 gene in mouse and human WAT. Genetic association study and expression quantitative trait loci analysis were combined to identify the phenotypic effect of CLSTN3 gene variant in humans. This was followed by mouse experiments using adeno-associated virus-mediated human CLSTN3 overexpression in inguinal WAT. We investigated the effect of CLSTN3 on WAT function and overall metabolic homeostasis, as well as the possible underlying molecular mechanism. Results: We observed that CLSTN3 gene was routinely expressed in human WAT and predominantly enriched in adipocyte fraction. Furthermore, we identified that the variant rs7296261 in the CLSTN3 locus was associated with a high risk of obesity, and its risk allele was linked to an increase in CLSTN3 expression in human WAT. Overexpression of CLSTN3 in inguinal WAT of mice resulted in diet-induced local dysfunctional expansion, liver steatosis, and systemic metabolic deficiency. In vivo and ex vivo lipolysis assays demonstrated that CLSTN3 overexpression attenuated catecholamine-stimulated lipolysis. Mechanistically, CLSTN3 could interact with amyloid precursor protein (APP) in WAT and increase APP accumulation in mitochondria, which in turn impaired adipose mitochondrial function and promoted obesity. Conclusion: Taken together, we provide the evidence for a novel role of CLSTN3 in modulating WAT function, thereby reinforcing the fact that targeting CLSTN3 may be a potential approach for the treatment of obesity and associated metabolic diseases.